DC characterization of advanced fine-filamentary MgB2 superconducting wires. (1st May 2022) - Kováč, P; Melišek, T; Kováč, J; Búran, M; Hušek, I; Rindfleisch, M; Tomsic, M
Abstract: MgB2 wires with 114, 192 and 342 filaments of size 14–19 µ m manufactured by HyperTech Research, Inc. have been subjected to low-temperature DC measurements. R ( T ), I – V characteristics, critical currents, stress and strain tolerances of these wires differing by filament architecture and filament size sheathed by resistive CuNi alloys were measured and compared with the literature data. It was found that these fine-filamentary wires have high engineering current densities not reduced by twisting up to 10 mm, sufficient strain tolerances and therefore are promising for future applications where minimized AC losses are required due to resistive sheaths, thin MgB2 filaments and short twist pitches.